Iptakalim confers an antidepressant effect in a chronic mild stress model of depression through regulating neuro-inflammation and neurogenesis. (September 2014) - Lu, Ming; Yang, Jing-Zhe; Geng, Fan; Ding, Jian-Hua; Hu, Gang
Abstract Depression is a serious mental disorder in the world, but the underlying mechanisms remain unclear and the effective cures are scarce. Iptakalim (Ipt), an ATP-sensitive potassium (K-ATP) channel opener that can cross the blood-brain barrier freely, has been demonstrated to inhibit neuro-inflammation and enhance adult hippocampal neurogenesis. But it is unknown whether Ipt is beneficial to therapy of depression by modulating neurogenesis and neuro-inflammation. This study aimed to determine the potential antidepressant efficacy of Ipt in a chronic mild stress (CMS) mouse model of depression. We showed that treatment with Ipt (10 mg/kg/day, i.p) for 4 wk restored the decrease of sucrose preference and shortened the immobile time in forced swimming tests (FST) and tail suspension tests (TST) in CMS model mice. We further found that Ipt reversed the CMS-induced reduction of the adult hippocampal neurogenesis and improved cerebral insulin signalling in the CMS mice. Furthermore, Ipt negatively regulated nod-like receptor protein 3 (NLRP3) expression and, in turn, inhibited microglia-mediated neuro-inflammation by suppressing the activation of NLRP3-inflammasome/caspase-1/interleukin 1β axis in the hippocampus of CMS mice. Taken together, our findings demonstrate that Ipt plays a potential antidepressant role in CMS model mice through regulating neuro-inflammation and neurogenesis, which will provide potential for Ipt in terms of opening up novel therapeutic avenues for depression.